Contemporary review of IgA nephropathy - Filippone, Edward J.; Gulati, Rakesh; Farber, John L. (Frontiers in Immunology, 2024)
IgA nephropathy (IgAN) is considered the most common primary glomerulonephritis worldwide with a predilection for Asian-Pacific populations and relative rarity in those of African descent. Perhaps 20 -50% of patients progress to kidney failure. The pathogenesis is incompletely understood. Mesangial deposition of immune-complexes containing galactose-deficient IgA1 complexed with anti-glycan IgG or IgA antibodies results in mesangial cell activation and proliferation, inflammatory cell recruitment, complement activation, and podocyte damage.Diagnosis requires a biopsy interpreted by the Oxford criteria. Additional pathologic features include podocytopathy, thrombotic microangiopathy, and C4d staining. Biomarkers predicting adverse outcomes include proteinuria, reduced GFR, hypertension, and pathology. Acceptable surrogate endpoints for therapeutic trials include ongoing proteinuria and rate of eGFR decline.The significance of persisting hematuria remains uncertain. The mainstay of therapy is supportive, consisting of lifestyle modifications, renin-angiotensin inhibition (if hypertensive or proteinuric), sodium-glucose-transporter 2 inhibition (if GFR reduced or proteinuric), and endothelin-receptor antagonism (if proteinuric). Immunosuppression should be considered for those at high risk after maximal supportive care. Corticosteroids are controversial with the most positive results observed in Chinese. They carry a high risk of serious side-effects. Similarly, mycophenolate may be most effective in Chinese. Other immunosuppressants are of uncertain benefit. Tonsillectomy appears efficacious in Japanese. Active areas of investigation include B-cell inhibition with agents targeting the survival factors BAFF and APRIL and complement inhibition with agents targeting the alternate pathway (Factors B and D), the lectin pathway (MASP-2), and the common pathway (C3 and C5).Hopefully soon the who and the how of immunosuppression will be clarified and kidney failure can be forestalled.